Recovery after homicide: narrative shifts in therapy with homicide perpetrators - Adshead, Gwen (Criminal justice and behavior, 2015)
A key theme in mental health is the principle of recovery. However, it is not clear how this might apply to forensic mental health services, which offer mental health care to men and women who have offended when mentally unwell. In this article, we explore how discussion of the index offense fits into recovery paradigms and how reflection on offender identity relates to recovery. Using clinical material from therapy groups for homicide perpetrators, we discuss how narratives of agency and responsibility change (or not) in therapy, and how narrative shifts link with the concept of ?recovery? in mental health.